(untitled) (Journal of the College of Basic Education, 2022)
The effect of extracts of the leaves of the capper spinosa plant on the snail Bulinus truncatus was studied. The study showed that there were different effects of the extracts of the leaves of the capper spinosa plant on the snail B. truncatus. These effects were represented by death, escape from the exposure medium, and a defect in the behavior of snails. The study also showed the possibility of using extracts of the leaves of the Shafallah plant to control the snail B. truncatus.